Simple Composition - Wuorinen, Charles (New York Edition Peters, 1994)
Originally published in 1979, this book was reissued by C. F. Peters Corporation in 1994. The author, the composer Charles Wuorinen, describes the book in this way : "--this book is written by a composer and is addressed to other composers - intending or actual, amateur or professional. Thus it is similar in intent to certain older books on the subject like Thomas Morley's "A Plain and Easie Introduction to Practical Musicke" (1597), for instance...It outlines present practice, and while it can be used for purely didactic purposes, it can also be employed in composing "real" music." "In writing this book, I intended it primarily as a guide for composers in search of practical advice and models of how one might work compositionally. But since my presentation made extensive use of the twelve-tone system in its simplest and most easily describable form, the book was taken as a primer in that system. The fact that I used twelve-tone relations for convenience and only because of their simplicity was somehow overlooked. Perhaps today in 1994 (the year this book was reissued after its first publication in 1979) the book may make a slightly different contribution than it originally did: to offer a basic outline of a musical system and method that has proved immensly rich since its introduction by Schoenberg seventy-five years ago, as well as to provide a few practical tips."
Keywords: Composing